Candidate regulators of early leaf development in maize perturb hormone signalling and secondary cell wall formation when constitutively expressed in rice - Wang, P; Karki, S; Biswal, A; Lin, H; Dionora, M; Rizal, G; Yin, X; Schuler, M; Hughes, T; Fouracre, J; Jamous, B; Sedelnikova, O; et al. (Springer Nature, 2017)
All grass leaves are strap-shaped with a series of parallel veins running from base to tip, but the distance between each pair of veins, and the cell-types that develop between them, differs depending on whether the plant performs C3 or C4 photosynthesis. As part of a multinational effort to introduce C4 traits into rice to boost crop yield, candidate regulators of C4 leaf anatomy were previously identified through an analysis of maize leaf transcriptomes. Here we tested the potential of 60 of those candidate genes to alter leaf anatomy in rice. In each case, transgenic rice lines were generated in which the maize gene was constitutively expressed. Lines grouped into three phenotypic classes: 1) indistinguishable from wild-type; 2) aberrant shoot and/or root growth indicating possible perturbations to hormone homeostasis; and 3) altered secondary cell wall formation. One of the genes in class 3 defines a novel monocot-specific family. None of the genes were individually sufficient to induce C4-like vein patterning or cell-type differentiation in rice. A better understanding of gene function in C4 plants is now needed to inform more sophisticated engineering attempts to alter leaf anatomy in C3 plants.